Prevalence and factors of COVID-19 among children in Hunan, China, following the deregulation of epidemic control: an observational study in epidemiology - Donghua Xie; Lijia Wan; Yixu Liu; Sanfeng Tan; Juan Xiao; Binbin Feng; Junqun Fang (BMJ Open)
Objectives To investigate the prevalence and factors of COVID-19 infection in children aged 0–6 years within Hunan Province following the deregulation of epidemic control.Design This is an observational study in epidemiology, using an on-site questionnaire survey to investigate the current status of COVID-19 infection and its influencing factors in children aged 0–6 years in Hunan Province from 16 February to 24 March 2023.Setting Multi-stage stratified sampling method was applied in this study. The regions were categorised as developed, medium and underdeveloped. One municipality was selected from each category. In each municipality, one district and one county were chosen for cluster sampling.Participants Children aged 0–6 years in Hunan Province.Results A total of 78 115 children aged 0–6 years were enrolled in this study, of 30 659 (39.2%) had a confirmed positive SARS-CoV-2 test result or related clinical symptoms. The majority of COVID-19 infections in children were of mild type (92.0%), and very few were severe and critical (0.4% and 0.1%). The majority (74.6%–88.7%) of children had minimal lifestyle behavioural changes after infected with COVID-19. Parents of the child working as a staff member (OR=0.654, 95% CI: 0.603, 0.709) and civil servant (OR=0.865, 95% CI: 0.794, 0.941), living in a rural area (OR=0.384, 95% CI: 0.369, 0.400) and no COVID-19 exposure (OR=0.108, 95% CI: 0.104, 0.113) were protective factors for COVID-19 infection in children.Conclusion Children experienced a large number of COVID-19 infections following the deregulation, fewer severe cases and fewer changes in lifestyle. Easing epidemic control measures in the later stage of the pandemic did not aggravate the consequences of the epidemic.